Islamic Capital Market a Catalyst For Sharia Investment: Sytematic Literature Review Using The Prisma Method - Santi Arafah; M. Shabri Abd. Majid; Sugianto (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
This research aims to analyze the Islamic capital market as a Catalyst For Sharia Investment. The method used in this research is a systematic literature review with the PRISMA approach with a time span of 2018-2025. The research analyzed 276 articles based on data obtained from google scholar and 46 of these articles were indexed by Scopus Q1, Q2, and Q3. And only 15 articles were eligible in this research. The results show that Islamic capital markets play an important role as a driver of Islamic investment by providing a forum for investors who want to invest according to sharia principles and become a source of financing for companies that operate according to sharia principles. Islamic capital markets also have a significant influence on a country's economy, especially in the field of investment because in the real sector, investment is considered to have a positive impact on the economy, so that if the development of the real sector increases, the country's production will also increase. One way a country can develop its real sector is by developing the financial sector.